Long-term Results of Nd: YAG Goniopuncture on Viscocanalostomy and Phacoviscocanalostomy. Issue 3 (March 2022) - Gupta, Chandni; Logeswaran, Abison; Mathews, Divya
Abstract : Précis: Laser goniopuncture (LGP) is an effective outpatient procedure which has been shown to maintain reduced intraocular pressure (IOP) 5 years following initial laser treatment in patients who have had viscocanalostomy (VC) (with or without phacoemulsification). Purpose: The purpose of this study was to establish the long term (5 y) efficacy of neodymium-doped:yttrium aluminum-garnet LGP to lower IOP following VC or phacoviscocanalostomy (PVC) in patients with glaucoma. Patients and Methods: This retrospective study analyzed patients who underwent LGP following VC±phacoemulsification between 2009 and 2012 at the Stanley Eye Unit in Abergele. Reason for further intervention included either increasing IOP outside target range or worsening visual fields. Statistical analyses were performed comparing pregoniopucture values to those taken up to 5 years later. Results: Of the 620 VC and PVC procedures performed between 2009 and 2012, 218 eyes underwent LGP after a mean of 25 months [95% confidence interval (CI): 22.58 to 27.41] following surgery. Patients having a PVC had a longer mean time to goniopuncture compared with those who were phakic and had VC only ( P <0.001). Immediately following goniopuncture IOP dropped, and a statistically significant reduction persisted at 5 year follow-up ( P <0.001). Goniopuncture reduced IOP significantly from a pretreatment value of 21 to 15 mm Hg over 5 years (95% CI) (χ 2 F (4) =119.1, P <0.001). In total, 154 eyes (71%) were commenced on IOP-lowering medication at a mean of 14 months (95% CI: 12 to 17). At 5 years, successful IOP control was achieved in 73% (49 of 67) of eyes. There was no difference found between type of surgery and successful pressure control at 5 years (χ 2 (1) =2.00, P =0.16). Conclusion: LGP is an effective procedure which maintains a statistically significant reduction in IOP in the long term.